(untitled) (Wallingford, UK, 1991)
This book provides an authoritative account of new developments in these disciplines as applied to such industries. It covers aspects of mechanical engineering such as tractor ride dynamics, soil-machine interaction and the stability of agricultural machinery on slopes, including climate modelling and control in greenhouses, and aspects of postharvest research such as heat and mass transfer in the drying and cooling of crops, damage in fruit handling and the extraction of protein from green crops. Chapters on abattoir design to improve animal welfare and biological waste treatment complete the book
Keywords: Agricultural engineering,Agricultural mechanics,Agricultural physics